Improved RNA preparation for RNA-seq of the intracellular bacterium Wolbachia wAlbB - Behrmann, Lara V.; Harbig, Theresa A.; Hoerauf, Achim; Nieselt, Kay; Pfarr, Kenneth M. (Frontiers in Microbiology, 2026)
Despite advances in RNA-seq, investigating the transcriptome of intracellular bacteria remains challenging due to the substantial presence of host RNA. In the case of Wolbachia spp. that are propagated in insect cell lines, commercially available rRNA depletion kits are often not suitable. Here, we describe a method to study the transcriptome of Wolbachia wAlbB in the Aedes albopictus cell line C6/36. Custom-designed riboPOOLs (siTOOLs Biotech) were used to remove both prokaryotic and eukaryotic rRNA. To enrich the bacterial mRNA, eukaryotic mRNA was depleted using Dynabeads (Thermo Fisher Scientific). Compared to RNA prepared using the Illumina Ribo-Zero Plus Depletion Kit alone, additional depletion of eukaryotic mRNA increased wolbachial reads 7-fold to 0.7% of all reads. After removing eukaryotic and prokaryotic rRNAs with custom-designed riboPOOLs, there was a 300-fold increase of reads that mapped to Wolbachia (30.2%). Combining customized rRNA depletion from both organisms with eukaryotic mRNA depletion was more cost-effective than simply increasing the number of sequencing reads. This method can potentially be used for the enrichment of bacterial mRNA in studies of intracellular bacteria that cannot be propagated in standard cell lines.